Emotional correlates of the basic traits of personality - Pacevičius, Jonas (Psichologija, 2005)
Most previous research has demonstrated relatively high correlations between two main traits – Extraversion and Neuroticism – and personality emotional predispositions. It has been shown that Extraversion and Emotional stability are predictors of positive emotions, while Introversion and Neuroticism are predictors of negative emotions (Costa & McCrae, 1980; Eysenck & Eysenck, 1985; Wilson & Gullone, 1999). However, some other research reveals the complexity and certain discrepancy of the above-mentioned links (Williams, 1993; McFatter, 1994; Matthews, 1998). The main aim of the present research is particularization of parameters of everyday emotional life in structures of two personality super factors: Extraversion and Neuroticism, i.e. examination the relationships between daily emotions indices and basic traits and types of personality. The second aim is to find out what influence the kind and character of everyday activity has on the relation between personality and emotions. In other words, the hypothesis of the research is that Extraversion and Neuroticism influence the modality structure of emotions, experienced during the concrete everyday activity. The method of chronological registration of everyday emotions, or „emotional diary“, has been used. For 2–4 weeks the 80 subjects (university students, aged 17–24 years) using special form have been chronologically registering the kind of everyday activity (learning, chores, aesthetic, spiritual activity, etc.), the sign, modality (joy, anger, fear, grief), intensity and duration of emotions. Personality traits were examined by EPI. Considerable emotional differences were found in subjects having high and low score in the both two scales. There were no significant differences between extraverts and introverts. Studying dynamics of subjects’ everyday emotions we found no correlation between neuroticism and index of emotional stability we obtained. Research revealed the specificity of the emotional regulation of kinds of everyday activities determined by the personality traits. However, they are not so expressed as it was expected. The most significant differences in the most kind of activities are revealed between stable extraverts and unstable introverts. Also, some important parameters of everyday emotional life (stability, intensity, hedonic level) and their relation with the basic personality traits are being discussed. The conclusion of the present research is as follows: the kind and character of everyday activities do not have a significant influence on the relation between the two personality super-factors – Extraversion and Neuroticism – and everyday emotions. The research has revealed that the link between the basic personality traits and everyday emotions tends to be stable enough, that is why it is little influenced by the character and specificity of everyday activity.